Implementasi Model Pembelajaran Kooperatif Tipe Jigsaw pada Mata Pelajaran PAI dalam Meningkatkan Hasil Belajar Siswa Kelas X di SMAN 2 Lubuk Alung - Sebrina, Dora; Rivauzi, Ahmad (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited research on the implementation of the Jigsaw cooperative learning model in the context of Islamic Education (PAI), despite the fact that low student participation in PAI classes significantly affects learning outcomes. The purpose of this study is to analyze the implementation of the Jigsaw model in enhancing student learning activity and its impact on cognitive, affective, and psychomotor learning outcomes in PAI subject in Class X-E1 at SMAN 2 Lubuk Alung. This research employed a descriptive qualitative method with an intrinsic single case study design. Participants included the PAI teacher and students of Class X-E1, selected through purposive sampling. Data were collected through participatory observation, semi-structured interviews, and documentation, then analyzed using an interactive analysis model involving data reduction, data presentation, and conclusion drawing. The results show that the implementation of the Jigsaw model, conducted with thorough planning and consistent teacher guidance, was able to improve student learning activity and achieve a learning mastery rate of up to 65%. These findings reinforce the theory that social interaction and individual accountability within groups support learning effectiveness. The main conclusion highlights the critical role of the teacher’s adaptive function as a facilitator in optimizing student collaboration through the Jigsaw model. The implications include theoretical contributions to the literature on collaborative-based PAI learning and practical recommendations for teachers to improve the quality of planning and implementation of cooperative learning.